Labor Market Regulations for Women : Are they Beneficial? - van Selm, Alexandra (World Bank, Washington, DC, 2012)
This note considers the impacts on female workers of two forms of labor market regulations common in developing countries: mandated maternity benefits and working-hour restrictions for women. Anecdotal evidence suggests that maternity benefits are unpopular with employers. Many developing countries also have working-hour restrictions specific to female workers. Such restrictions are usually motivated by concerns for women's health and safety.